2003
DOI: 10.1007/3-540-45110-2_61
|View full text |Cite
|
Sign up to set email alerts
|

Generative Representations for Evolving Families of Designs

Abstract: Abstract. Since typical evolutionary design systems encode only a single artifact with each individual, each time the objective changes a new set of individuals must be evolved. When this objective varies in a way that can be parameterized, a more general method is to use a representation in which a single individual encodes an entire class of artifacts. In addition to saving time by preventing the need for multiple evolutionary runs, the evolution of parameter-controlled designs can create families of artifac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 11 publications
0
43
0
Order By: Relevance
“…Hornby looked at a wide variety of representation schemes for generative design [4], including "virtual creatures" generated using a variant of L-systems. Hornby and others [2] have observed that the generative reuse of parameterised elements in encoded designs improves the ability of an evolutionary algorithm to search large design spaces.…”
Section: Related Workmentioning
confidence: 99%
“…Hornby looked at a wide variety of representation schemes for generative design [4], including "virtual creatures" generated using a variant of L-systems. Hornby and others [2] have observed that the generative reuse of parameterised elements in encoded designs improves the ability of an evolutionary algorithm to search large design spaces.…”
Section: Related Workmentioning
confidence: 99%
“…Boers and Sprinkhuizen-Kuyper [15] used a string L-system to also evolve ANNs by interpreting the final string that results from a given number of rewrites as a graph. The grammar of GENRE [16], an evolutionary design framework based on a parametric L-system, is evolved by a simple EA with specialized operators. Strings are rewritten and then translated into designs, with successful application to table designs, neural networks, and robot controllers.…”
Section: Grammatical Developmentmentioning
confidence: 99%
“…Some researchers tried to systematize and compare arti cial genetic encodings in a single phenetic model [28,6,20,15]. This allows to test their performance in the same environment, and thus focus on the characteristics of the encodings (features like their complexity, constraints, support for modularity, body symmetry, compression, redundancy, etc.).…”
Section: Genetics In Arti Cial Life Systemsmentioning
confidence: 99%
“…The freedom in designing and using various genetic encodings allows researchers to compare them and study their properties in a single simulation model [28,6,15,20]. If many genetic encodings exist in a single simulation model, then each of them must be capable of expressing phenotypes in that model.…”
Section: Introductionmentioning
confidence: 99%